Integration of Open-Source Software (Koha, Greenstone and DSpace) with Library Discovery System (VuFind): A Future Library Solution - Bhowmick, Anupam; Chakrabarty, Baishakhi (Journal of Information and Knowledge, 2021)
This paper demonstrates the design, workflow and integration methodology of open-source ILS (Koha), Digital library software (Greenstone), Institutional repository (DSpace) with open-source library discovery software (VuFind). A methodology of integration has been explained using available standards and technology. Main purpose of this research is to demonstrate single-window search interface, harvesting of metadata and full-text of resources. Integration of open-source library software with the discovery system (VuFind) can result significant cost reduction when compared with commercial discovery systems.